The Four Way Mode to Drive a Vehicle - Dr. P. Seshu Mani; VSVG. Theekshana (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Electric energy alone is not sufficient for vehicles to travel long distances, as a fully charged battery typically provides a range of only 60 to 100 km. To extend the mileage, four types of energy sources can be used together. These include electric energy, solar energy, wind energy, and generator (dynamo) energy. By combining these renewable sources, vehicles can travel continuously over long distances without stopping.